Morphological characterization and genetic identity of crop wild relatives of rice (Oryza sativa L.) collected from different ecological niches of India - Tiwari, Shailesh; Yadav, Mahesh C.; Dikshit, Nilamani; Yadav, Vijay K.; Pani, Dipti R.; Latha, M. (Genetic resources and crop evolution, 2020)
Crop wild relatives of rice ( Oryza sativa L.) are an important reservoir of genes for broadening the genetic base of commercial varieties. India is the centre of genetic diversity of some of the wild as-well-as the cultivated rice species. In order to collect genetic diversity, explorations were undertaken in six states located in different agro-ecological zones of India. Forty-four accessions belonging to four wild species ( Oryza rufipogon Griff., Oryza nivara Sharma et Shastry, Oryza officinalis Wall. ex Watt and Oryza sativa L. f. spontanea Roshev.) including two accessions of cultivated rice ( Oryza sativa L. subsp. indica Kato) were collected from different ecological niches. The rice accessions were characterized using 28 morphological descriptors, which included 15 qualitative and 13 quantitative traits. Wild rice accessions displayed a broad range of phenotypic variation for plant height, main heading days, days to 50% flowering, flag-leaf length and width, panicle shape and size, peduncle length, awning pattern, awn length and colour, seed length and width, seed length/width ratio and 100-seed weight. Cluster analysis based on Jaccard’s similarity coefficients derived from 28 morphological traits grouped 44 accessions into three clades. DNA sequencing revealed that internal transcribed spacer (ITS) region of 18S–5.8S–28S nuclear ribosomal cistron varied from 574 to 577 bp with mean of 576.1 bp in AA-genome species. GC content was high in ITS region, which varied from 69.57 to 70.36% with mean value of 69.99%. Neighbour-joining phylogenetic tree distinguished Oryza sativa – nivara – rufipogon complex from other species of AA-genome. The wild germplasm characterized in this study could be utilized in the genetic enhancement of cultivated rice.